Evaluation and Modelling of Shallow Subsurface Temperature in Parts of Akwa Ibom State, Nigeria. - Umoh, Edikan S.; Emujakporue, Godwin O.; Sofolabo, Adekunle O.; Jonah, Udeme E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: Soil temperature is one of the most important factors affecting plant growth. Until soil reaches a certain critical temperature neither seeds germinate nor plants have a normal growth because it affects root and shoot growth and availability of water and nutrients. Methods: Temperature measurements have been carried out at different depths in the soil in parts of Akwa Ibom State of Nigeria. Different locations were chosen, (Ikot Obong Edong, Ikot Otu, Abiakpo). Results of measurements were taken from different depths and different time with the aid of a soil thermometer over a period of one year. The diurnal soil temperature cycles are being modelled with fairly good accuracy. Differences in measured and modelled soil temperatures are determined at daily levels at depths 0cm which is the top soil, 10cm, 30cm and 50cm. Results: The daily soil temperature ranges from 29.7? – 42.9? for months covering dry season with a simple mean of 36.3?; 21.2?– 29? for months covering rainy season with a simple mean of 25.1. The mean temperature for all season is 30.7?, indicating that these locations are favourable for farming. Conclusion: The results can be valuable in planning and developing soil tillage practices and other agricultural activities in the areas studied. It was found that in dry season, the soil temperature increases with depth and in rainy season, it first decreases up to certain depth and then starts to increase with depth. This is due to the effects of solar thermal energy and ground thermal energy.